DTA-TGA, crystal and molecular structure determination and vibrational studies of potassium nitroprusside sesquiquarterhydrate, K2[Fe(CN)5NO]·1.25H2O - Amalvy, Javier Ignacio (1986)
The crystal structure of the title compound has been determined from diffractometer data and refined with isotropic thermal parameters to final R w factors of R = 0.058 and Rw = 0.056. It crystallizes in the orthorhombic space group p212121 (No. 19), with a = 9.706(7), b = 18.826(6), and c = 25.258(6) A. The asymmetric unit contains four nitroprusside ions, eight potassium ions, and five water molecules, one of which shows disorder. The infrared spectra of the polycrystalline compound, both normal and with different degrees of deuteration at temperatures ranging from liquid nitrogen to room temperature, were obtained. The vibrational spectra present an unusual number of fundamental and first overtone NO stretching bands and a rich structure in the water bending region, in accordance with the existence of inequivalent nitropmsside ions and water molecules.